Effects of moderate physical activity on diabetic adhesive capsulitis: a randomized clinical trial - Sheikh,Raheela Kanwal; Toseef,Amna; Omer,Aadil; Aftab,Anam; Haider Khan,Muhammad Manan; Ayaz,Saeed Bin; Althomli,Omar; Razzaq,Aisha; Khokhar,Samra; Jabbar,Nazia; Awan,Waqar Ahmed (PeerJ, 2024)
Background Moderate physical activity (MPA) has proven advantages for glycemic control, cardiovascular health, and functional independence. However, physical activity is not part of routine conventional physical therapy (CPT) in managing diabetic adhesive capsulitis patients. Objective To determine the effects of moderate MPA on diabetic adhesive capsulitis (AC). Methodology A randomized control trial was conducted at the Combined Military Hospital (CMH), Muzaffarabad, Pakistan from March 2022 to October 2022. A total of n = 44 patients with diabetic AC, aged 40 to 65 years, HbA1c > 6.5% were enrolled. Group A received MPA and CPT, while Group B only received CPT for six weeks. The upper extremity function, pain, and range of motion were assessed at baseline, third week, and sixth week through the disability of arm, shoulder, and hand (DASH) questionnaire, numeric pain rating scale (NPRSS), and goniometer respectively. Results The NPRS score and ROMs showed significant improvement (p < 0.05) in group A compared to group B with a large effect size. When comparing the mean difference of the DASH score (73 + 7.21 vs. 57.9 + 12.64, p < 0.001, Cohen’s d = 1.46) was significantly improved with large effect size in group A as compared to group B. Conclusion MPA along with CPT has positive effects on patient pain, range of motion, and disability in patients with diabetic adhesive capsulitis.
Keywords: Adhesive capsulitis; Frozen shoulder; HBA1c; Physical therapy; Physical activity; ROMs; Shoulder function